Stakeholders participation in tourism and recreation planning and management in protected areas: Fundamentals on the participatory process - Rosa, Paulo Filipe (2016)
Tourism and recreation in protected areas is becoming increasingly relevant at an international and national level. Therefore, it is important that these areas adopt principles of planning and management of tourism and recreation practices in order to better fit in this growth and contribute to the sustainable development of the territories. Regarding management, we found participatory management as an essential condition for the achievement of sustainability principles. This article reflects a literature review regarding a better understanding of the fundamentals governing these processes. The reflections made in this article stress, along with procedural aspects, the importance of a profound understanding of the stakeholders profile, based on active communication and legitimacy to participate. It considers that an adequate understanding of the stakeholders profile and perspectives about the several factors of the management process may reduce the most common problems deriving from its implementation.